The Influence of Gender Roles and Coping Strategies to The Fishermen’s Family Happiness Index - Rona Aulia Karimah; Herien Puspitawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
Seasonal changes will have an impact on the lives of fishermen’s families, especially the economic sector. Changes in the sea and non-sea seasons have an impact on family cooperation in survival. These effects will be seen in the gender role of husband and wife in solving problems in fishermen’s families. This study aims to analyze the effect of gender roles and coping strategies on fishermen’s family happiness index. The study design used a cross-sectional study with interviews and questionnaire assistance. The research sample was selected by purposive sampling with respondents of 40 fishermen’s families in the Toboali District, Bangka Belitung Islands Province. The gender role variables, coping strategies, and fishermen’s family happiness index are in the medium category. There is a correlation between coping strategies with the happiness index of fishermen’s families. The number of family members shows a significant negative effect on the happiness index in the sea and non-sea seasons. Meanwhile, coping strategies present a significant positive effect on the happiness index of fishermen’s families in the sea and non-sea seasons.